2011
DOI: 10.1136/annrheumdis-2011-200281
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis reveals specific changes in osteoarthritis synovial fibroblasts

Abstract: Cultured OASFs display a more homogeneous transcriptomic profile than RASFs when compared to HSFs. This supports the participation of synovial fibroblasts in the pathogenesis of OA and may reflect global defects in the mesenchyma-derived lineages of the different tissues in OA joints. These data support individual heterogeneity among RASFs and advise against the use of OASFs as controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…Subsequent functional studies showed that LBH expression in FLS is regulated by platelet‐derived growth factor, a major growth factor that contributes to synovial lining hyperplasia in RA . Low levels of LBH expression, which have previously been documented for RA FLS , regulates the cell cycle and can contribute to a hyperproliferative state of RA FLS. Understanding why low LBH expression levels could participate in RA pathogenesis can provide insight into disease mechanisms and possibly novel therapeutic targets.…”
Section: Discussionmentioning
confidence: 93%
“…Subsequent functional studies showed that LBH expression in FLS is regulated by platelet‐derived growth factor, a major growth factor that contributes to synovial lining hyperplasia in RA . Low levels of LBH expression, which have previously been documented for RA FLS , regulates the cell cycle and can contribute to a hyperproliferative state of RA FLS. Understanding why low LBH expression levels could participate in RA pathogenesis can provide insight into disease mechanisms and possibly novel therapeutic targets.…”
Section: Discussionmentioning
confidence: 93%
“…For each analysis, eight raw fluorescence data files with gpr extension, obtained after scanning and corresponding to four exposed cultures and four control cultures, were submitted to GeneSpring software GX11 (Agilent Technologies) as follows. Concerning the statistics methodology, we used a widespread method for determining the significance change of gene expression [32]. The raw data were first normalized using the percentile shift 75 normalization method.…”
Section: Methodsmentioning
confidence: 99%
“…Many investigators have explored gene expression changes in OA by transcriptomic profiling of human joint tissues (). While these studies have yielded important information on candidate genes in advanced OA, there are drawbacks to using patient tissue for expression profiling.…”
mentioning
confidence: 99%